1984
DOI: 10.1098/rstb.1984.0037
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of calcification in the marine alga Emiliania huxleyi

Abstract: Coccoliths are delicate calcified structures produced by marine unicellular algae. In the species Emiliania huxleyi the calcium carbonate (mostly calcite) is closely associated with a complex, acidic polysaccharide which binds calcium ions specifically, interferes with the in vitro crystallization of calcium carbonate, and appears to be bound to a positively charged protein before the crystallization process is finished. Ultra-high resolution electron microscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(45 citation statements)
references
References 16 publications
2
43
0
Order By: Relevance
“…Coccoliths form an elaborate shell around the cells. They are produced intracellularly in a specialized vacuole (Westbroek et al, 1984), then extruded and incorporated into an extracellular coccosphere. Coccoliths are shed continuously, however, when the cell dies or lyses, large concentrations of coccoliths are detached and the surrounding water turns a characteristic milky white and it is during this period the bloom can be easily observed by satellite imagery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coccoliths form an elaborate shell around the cells. They are produced intracellularly in a specialized vacuole (Westbroek et al, 1984), then extruded and incorporated into an extracellular coccosphere. Coccoliths are shed continuously, however, when the cell dies or lyses, large concentrations of coccoliths are detached and the surrounding water turns a characteristic milky white and it is during this period the bloom can be easily observed by satellite imagery.…”
Section: Discussionmentioning
confidence: 99%
“…Emiliania huxleyi can be easily viewed by satellite imagery (Figure 1) since they are characterized by high light backscatter caused by coccoliths, elegant calcium carbonate scales, which E. huxleyi produces intracellularly and sequesters over its cell surface (Westbroek et al, 1984). Whilst E. huxleyi is blooming it is constantly producing and shedding coccoliths into the surrounding water.…”
Section: Introductionmentioning
confidence: 99%
“…Crystal growth is tightly controlled by the cellular machinery. The inner side of the CV membrane always remains in close contact with the coccolith and is actively expanded from the outside by the cytoskeleton located within the cytosol so that the growing calcite crystals fill the space defined by the expanding vesicle (Westbroek et al, 1984(Westbroek et al, , 1989Didymus et al, 1994;Marsh et al, 1994;Young et al, 2009). Inside the CV, coccolithassociated polysaccharides (CAPs) bound to the inner side of the membrane, have a crucial role in controlling CaCO 3 precipitation due to their potential to bind Ca 2+ (De Jong et al, 1976) and inhibit precipitation at places where they cover the calcite (Borman et al, 1982;Henriksen et al, 2004).…”
Section: Cause Of Malformationsmentioning
confidence: 99%
“…The formation takes place in a Golgi-derived vesicle (coccolith vesicle or CV) which is closely associated with a labyrinthine membrane system (reticular body). Coccolith formation is initiated inside the CV with the production of an organic base plate which serves as template (van der Wal et al, 1983;Westbroek et al, 1984Westbroek et al, , 1989Young et al, 1999). Nucleation of calcite occurs subsequently on the rim of the organic base plate from where the initial crystals start to grow in a radial direction until coccolith formation is completed (Westbroek et al, 1984(Westbroek et al, , 1989Young et al, 1992).…”
Section: Cause Of Malformationsmentioning
confidence: 99%
“…39 Similarly, CaCO 3 nanoplates assemble into necklace-like structures in the early stage of coccolith formation. 40 Such a controlled assembly of colloidal particles that act as building units have recently attracted much attention in materials science. 41 It has been found that colloidal silica nanospheres (SNSs) assemble into one-dimensional (1D) chain-like structures in water with the aid of a block copolymer, as described below.…”
Section: Silica Nanoparticles Self-assembled Into Chain-like Structuresmentioning
confidence: 99%